Withholding effort in sharing knowledge in online space: differential effects of task characteristics. Issue 10 (3rd September 2020) - Wu, Dongming
Abstract : Purpose: Knowledge withholding is an important but under-studied topic, which refers to the phenomenon that individuals give less than full effort to contributing knowledge. This study aims to investigate the differential effects of task characteristics on individuals' knowledge withholding behavior in online space, this study develops and empirically verifies a theoretical model that covers the five core task characteristics in job characteristics model (autonomy, identity, feedback, skill variety and significance), knowledge sharing self-inefficacy and withholding effort in sharing knowledge. Design/methodology/approach: Using an online survey method, this study collected empirical data from 351 general internet users from 30 provincial administrative units in China. The data were analyzed using the structural equation modeling technique of partial least squares. Findings: The analysis results indicate that autonomy negatively affects, while identity, skill variety and significance positively affect users' knowledge withholding behavior in online space through the mediation of knowledge sharing self-inefficacy, and that three task characteristics (autonomy, identity and feedback) strengthen the relationship between knowledge sharing self-inefficacy and knowledge withholding. Practical implications: This study provides valuable insights for reducing knowledge withholding behavior in online space. Operationally, different levels of task characteristics such as autonomy, identity and feedback can be set to prevent users from perceiving themselves as inefficacious, and to weaken the behavioral expression of knowledge sharing self-inefficacy. Originality/value: This study provides a comprehensive understanding of the differential effects of task characteristics on knowledge withholding in online space, and improves the cognition of the boundaries of withholding effort in sharing knowledge in online space.